Permainan Tradisional terhadap Perkembangan Motorik Kasar Anak pada Disibilitas Tuna Grahita - Dzakiyyah, Dwi Manna Nasmi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to evaluate the positive impact of traditional games on the gross motor development of children with intellectual disabilities through a literature review. The method employed was a literature study, analyzing relevant journals and theoretical references. The research findings indicate that traditional games play a crucial role in enhancing gross motor skills in children with intellectual disabilities, including balance, coordination, body movements, muscle strength, and other gross motor abilities. Traditional games provide varied movement stimuli, involving body coordination, and increasing children's participation in physical activities. Through traditional games, children with intellectual disabilities can improve their gross motor abilities, gain better self-confidence, and enhance social interaction with peers. Therefore, traditional games significantly contribute to the development of gross motor skills in children with intellectual disabilities. It is important to pay attention to and implement traditional games in the education and rehabilitation of children with intellectual disabilities. The implementation of traditional games can help improve the quality of life for these children by enhancing their gross motor skills and facilitating participation in physical activities. Thus, traditional games have the potential to be a valuable component in intervention programs for children with intellectual disabilities. Keywords: Intellectual Disabilities, Gross Motor Development, Literature Review, Traditional Games.